An Exploration of the Range of Noise Intensity That Affects the Membrane Potential of Neurons - Rubin Wang; Guanzheng Wang; Jinchao Zheng (Abstract and Applied Analysis)
Neuronal activity in the human brain occurs in a complex physiologic environment, and noise from all aspects in this physiologic environment affects all aspects of nervous-system function. An essential issue of neural information processing is whether the environmental noise in a neural system can be estimated and quantified in a proper way. In this paper, we calculated the neural energy to estimate the range of critical values of thermal noise intensity that markedly affect the membrane potential and the energy waveform, in order to define such a noisy environment which neuronal activity relies on.